The Phosphorus Economy of Mediterranean Oak Saplings Under Global Change - Dirks, Inga; Köhler, Julia; Rachmilevitch, Shimon; Meier, Ina C. (Frontiers in Plant Science, 2019)
While a severe decrease in phosphorus (P) availability is already taking place in a large number of ecosystems, drought and nitrogen (N) deposition will likely further decrease the availability of P under global change. Plants have developed physiological strategies to cope with decreasing P resources, but it is unclear how these strategies respond to elevated N deposition and summer droughts. We investigated the influence of N and P availability and soil drought on P uptake (H333PO4 feeding experiment) and use efficiencies in young Quercus calliprinos Webb. trees. We hypothesized that (H1) the expected increases in soil N:P ratios will increase the efficiencies of P uptake and use of oak saplings but will decrease the efficiencies of N uptake and use, whereas (H2) drought will affect P uptake efficiency more than N uptake efficiency. In confirmation of (H1) we found that a sharp increase of the soil N:P ratio from 4 to 42 g g-1, significantly increased the instantaneous 33P uptake efficiency (33PUptakeE) by five-fold and long-term P uptake efficiency (PUptakeE) by six-fold, while it decreased N uptake efficiency (NUptakeE) and N use efficiency (NUE). In contradiction to (H1), P use efficiency (PUE) did not respond to the simulated extended gradient of soil N:P ratios but remained relatively constant. (H2) was only partially confirmed as soil drought reduced PUptakeE by up to a fourth at high soil N:P ratios but had no significant effect on NUptakeE. As a consequence, increasing summer droughts may decrease the response of PUptakeE to increasing P limitation, which – in the absence of adjustments of the efficiency of P use – can aggravate growth reductions in this eastern Mediterranean tree species under global change.